Framework for climate resilience in food systems with a gendered lens - Tank, Nikita; Vishwanath, Drishti; Choudhary, Anjali (Indian Institute of Management, 2023)
With the acknowledgment of climate change as a key development concern, the concept of climate resilience to combat its impacts has gained research and policy impetus. Further, there has been a growing emphasis on gender in climate resilience, given that women are documented as experiencing greater vulnerabilities and adaptation challenges. In the domain of agriculture and food systems, various studies develop a conceptual framework, as well as identify resilience indicators within these; for example, Waldick identifies key drivers of climate resilience (governance, demographics, markets, etc.) within a framework, and Lipper identifies potential pathways of climate-smart agriculture (CSA). Huyer expands Lipper’s framework to integrate gender and social inclusive dimensions. Given the multiplicity of interpretations and frameworks, this study seeks to: (a) examine the existing frameworks on climate resilience and gender in food systems through a systematic review, and (b) build on and strengthen these to develop an encompassing framework considering various contexts and intersectionalities, drawing from field learnings in Odisha, India. This is a mixed-methods study including secondary data and information synthesis, focus group discussions and qualitative interviews of stakeholders in food systems. The framework can serve as a comprehensive conceptual and practical diagnostic tool for policymakers to apply across different agriculture and food subsystems (such as crops, livestock, fisheries and aquaculture), for local and state contexts.